DEVELOPMENT OF METHODOLOGY FOR CAPACITY CALCULATION IN THE SECTIONS WITH AN INTERMEDIATE JUNCTION (Perner's Contacts, 2011)
This article deals with the methodology of capacity calculation in the crossing or overtaking sections with one or more junctions. The basic methodology adumbrated in (1) is developed with emphasis on thorough specification of input data and the process of setting total time of occupancy of observed line with successive trains.